ANALYSIS OF THE APPLICATION OF INCOME TAX ACCOUNTING PPh 21 THE SALARY OF EMPLOYEES AT VITKA POINT BATAM SPBU - Ita Mustika; Ferdila; Khadijah; Viola Syukrina E Janrosl (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
SPBU Vitka Point is a company engaged in the fuel retail sector in Batam City. SPBU Vitka Point deducts PPh 21 every month from employee income. The goal to be achieved in this study is to analyze whether the calculation, determination, and reporting of PPH 21 Income Tax for employees at the Vitka Point gas station are by the Law on the Harmonization of Tax Regulations No. 7 of 2021 (Chapter III). The research was conducted using descriptive qualitative methods and data collection techniques using observation, documents, and interviews. The Vitka Point gas station uses a withholding tax system withholding tax. The calculation of PPh 21 at the Vitka Point gas station for income received regularly by employees is correct and by the provisions of the applicable Law.